Phenomenon of twist drill - Vasilko, Karol; Simkulet, Vladimír (Manufacturing Technology Journal, 2012)
In 1770 an Englishman, P. Cooke, had a twist drill patented, a tool, which has such specifications at its application, that are not typical for other tools, in spite of its defined geometric shape. During drilling it behaves like a helical spring, it turns as a result of cutting resistance after first turn and it tries to screw off and screw in, which leads to the occurence of torsional vibration. Cutting speed changes considerably along the cutting edge of the drill, by which the coefficient of friction with drilled material and cutting wedge wear change as well. A built-up edge on the face area occures on certain section of cutting edge and it tears off. By this cutting conditions change, working face angle, radius of "plastic" tip of the built-up edge and the quality of surface of drilled hole. These specific phenomena are identifiend in the paper.
Keywords: cutting; drilling; quality of surface; tool wear